OK - OKAY - Wahler, Marc-Olivier (New York : Grey Art Gallery NYU New York SI (Swiss Institute - Contemporary Art New York), 2005)
Andersson, Christian ; Blanckart, Olivier ; Carron, Valentin ; Favaretto, Lara ; Gramsma, Bob ; Grasso, Laurent ; Gussin, Graham ; Kessler, Leopold ; Matteo, Gabriele Di ; McEwen, Adam ; Reiterer, Werner ; Solakov, Nedko ; Verna, Jean-Luc ; Woodeson, Ben
Press Clips p. 154-155
Engels
Exhibition. OK. Exhibition. OKAY. Grey Art Gallery NYU New York. SI (Swiss Institute - Contemporary Art New York). 2005-04-19. 2005-07-16. 2005-07-16
boek